An Unspoken Trust – Violated? - Kia Jane Richmond (Journal of the Assembly for Expanded Perspectives on Learning, 2003)
Reflecting on our decisions in the classroom, both when we are honest with our students & when we are not, can offer teachers opportunities for growth and change.